2023
DOI: 10.3390/ph16030328
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Potential of a Plant-Based Substance for the Treatment of Seborrheic Dermatitis

Abstract: Seborrheic dermatitis (SD) is the most prevalent dermatological disease, occurring in up to 50% of newborns, children, and adults around the world. The antibacterial and antifungal resistance contributed to the search for new natural substances and the development of a novel substance based on Melaleuca alternifolia (M. alternifolia) leaf oil (TTO), 1,8-cineole (eucalyptol), and α-(-)-bisabolol. Thus, this work aimed to determine the chemical composition of the novel plant-based substance and to evaluate its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 73 publications
0
19
0
2
Order By: Relevance
“…The major biologically active compounds were terpinen-4-ol (20.88%), 1,8-Cineol (22.28%), (-)-α-bisabolol (25.73%) and o-cymene (8.16%). This substance revealed inhibitory effects against the yeast Malassezia furfur , which is a main pathogen involved in the pathogenesis and manifestation of the dermatological disease Seborrheic dermatitis [ 52 ].…”
Section: Anti-microbial and Anti-viral Potentialmentioning
confidence: 99%
“…The major biologically active compounds were terpinen-4-ol (20.88%), 1,8-Cineol (22.28%), (-)-α-bisabolol (25.73%) and o-cymene (8.16%). This substance revealed inhibitory effects against the yeast Malassezia furfur , which is a main pathogen involved in the pathogenesis and manifestation of the dermatological disease Seborrheic dermatitis [ 52 ].…”
Section: Anti-microbial and Anti-viral Potentialmentioning
confidence: 99%
“…Their respective zone of inhibition is listed in Table 3. In order to compare the antifungal effectiveness, the study was refined taking similar concentration of standard drug, KTZ 40,41 . The zone of inhibition for KTZ (0.161 mg/mL) was not observed, whereas ZnO nanoparticles coated with an equivalent amount of KTZ has shown the zone of inhibition (25 mm) (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been shown, in secretory otitis media (SOM), that different inflammatory mediators, such as CXCL1, IL-16, IL-8, IL-17, IL-1β, CXCL10, and CXCL9, were found in high concentrations in middle ear fluids, in association with the presence of bacterial and viral nucleic acid levels [ 36 ]. Moreover, it has recently been shown that 1,8-Cineol contributes to a synergistic anti-microbial and also anti-fungal activity within a novel substance based on Melaleuca alternifolia leaf oil, which showed inhibitory effects against the pathogenic yeast Malassezia furfur , which is involved in the dermatological disease, Seborrheic dermatitis [ 37 ]. In this context, 1,8-Cineol may be a potential alternative to conventional fungicides, since different fungal citrus pathogens have been shown to develop tolerance to conventional fungicides but not to 1,8-Cineol [ 38 ].…”
Section: Discussionmentioning
confidence: 99%